Education Attainment of the Working-Age Population of Moscow According to the Population Census - V. G. Semenova; A. E. Ivanova (Здоровье мегаполиса)
Background. As a separate constituent entity of the Russian Federation, Moscow is characterized by significant heterogeneity of the population and its determinants of health, largely due to socioeconomic factors, the most important of which is the educational status of the population. Considering that the main contribution to the trends in life expectancy is made by the workingage population, the purpose of the study is to analyze the difference in the level of education of certain age groups in the districts and municipalities of Moscow. The data was obtained from the Population Census 2021. The highest educational qualification is observed in the Central and Western parts of Moscow, including the recently incorporated Novomoskovskiy Administrative Okrug (administrative district), while the residents of the Southern, Zelenogradskiy, and Troitskiy Administrative Okrugs have the lowest educational qualification. At the same time, there is a mixed education trend: on the one hand, the centripetal force in educational qualification is prevalent (the closer the center, the higher the educational qualification); on the other hand, dispersed settlement is being formed. As a result, the highest qualification levels are observed in remote areas of the capital, while the lowest are shifting to the center. From a social point of view, special attention should be paid to territories with the maximum share of both highly and poorly educated populations, especially considering the similar situation in the Central Administrative Okrug.